BurnBLITZ version II: a personalised fitness app revolutionising exercise and combating obesity among university students - Md Radzi, Noor Azila Azreen; Mohamed, Muhamad Noor; Raja Hussain, Raja Nurul Jannat; Saiful Annur, Muhamad Safiq; Adnan, Mohd Aizzat; Shari, Maisarah (Faculty of Pharmacy, 2025)
With Malaysia facing one of the highest obesity rates in Southeast Asia (20.1% of adults are classified as obese), fitness apps have gained popularity as tools to promote healthier lifestyles. BurnBLITZ Version II (V2), a personalised exercise app, was developed to address obesity among university students by offering tailored workout plans, instructional videos, and cloud-based updates for safe and effective training. A trial involving 150 students selected based on body mass index (BMI)and willingness to volunteer was conducted. Participants were divided into two groups: one using the apps (n=75) and a control group (n=75). Pre-and post-tests assessing cardiovascular fitness, muscular strength, and endurance significantly improved in the app-assisted group (p<0.05). Unlike typical fitness apps, BurnBLITZ V2 provides expert consultations, offering personalised guidance to enhance user engagement and motivation. This feature makes it particularly beneficial for university students with busy schedules, helping them integrate exercise into daily routines. By addressing common fitness barriers like time management and commitment, BurnBLITZ V2 presents a promising solution for combating obesity through accessible, engaging, and personalised fitness support.